Seasonal Regulation of Petal Number. Issue 2 (31st August 2017) - McKim, Sarah M.; Routier-Kierzkowska, Anne-Lise; Monniaux, Marie; Kierzkowski, Daniel; Pieper, Bjorn; Smith, Richard S.; Tsiantis, Miltos; Hay, Angela
Abstract : The number of petals in hairy bittercress flowers varies according to seasonal changes in the environment such as spring versus summer temperatures. Abstract: Four petals characterize the flowers of most species in the Brassicaceae family, and this phenotype is generally robust to genetic and environmental variation. A variable petal number distinguishes the flowers of Cardamine hirsuta from those of its close relative Arabidopsis ( Arabidopsis thaliana ), and allelic variation at many loci contribute to this trait. However, it is less clear whether C. hirsuta petal number varies in response to seasonal changes in environment. To address this question, we assessed whether petal number responds to a suite of environmental and endogenous cues that regulate flowering time in C. hirsuta . We found that petal number showed seasonal variation in C. hirsuta, such that spring flowering plants developed more petals than those flowering in summer. Conditions associated with spring flowering, including cool ambient temperature, short photoperiod, and vernalization, all increased petal number in C. hirsuta . Cool temperature caused the strongest increase in petal number and lengthened the time interval over which floral meristems matured. We performed live imaging of early flower development and showed that floral buds developed more slowly at 15°C versus 20°C. This extended phase of floral meristem formation, coupled with slower growth of sepals at 15°C, produced larger intersepal regions with more space available for petal initiation. In summary, the growth and maturation of floral buds is associated with variable petal number in C. hirsuta and responds to seasonal changes in ambient temperature.